International strategic alliance partner selection process in Malaysia - Abdul Ghani, Ahmad Bashawir; Subhan, Muhammad (2010)
A study argues that the motivation involved in partner selection must be distinguished from the motivation to enter into a strategic alliance; the latter may be considered the "ends" dimension of motivation while the former is concerned with "means". Thus it is important to distinguish between "task related" factors and "partner related" factors in analyzing the partner selection process. Based on a survey of 42 international strategic alliances in Malaysia, respondents rank partner related factors as significantly more important than task factors in selecting a partner.The existence of partner related factors as a separate construct is also confirmed by factor analysis.Further, this study indicates that respondents' factor scores on four factors are significantly related to the corporate history and characteristics of the corporate partner, and to the personal characteristics of the CEO.